2016
DOI: 10.4102/phcfm.v8i1.913
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable disease risk factors and treatment preference of obese patients in Cape Town

Abstract: BackgroundInsights into the characteristics of treatment seekers for lifestyle changes and treatment preferences are necessary for intervention planning.AimTo compile a profile of treatment-seeking obese patients with non-communicable diseases (NCDs) or NCD risk factors and to compare patients who choose group-based (facility-based therapeutic group [FBTG]) versus usual care (individual consultations) treatment.SettingA primary healthcare facility in Cape Town, South Africa.MethodsOne hundred and ninety-three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…which was a survey restricted to adults 35 years and older[ 8 ]. Manning et al (2016) identified a much higher prevalence rate of 69% for total cholesterol elevation (though a lower threshold of 4.5mmol/L) in Cape Town, but this was for obese subjects with ages 18 and older[ 9 ]. Finally, Maimela et al(2016) performed a survey of 20–59 year old subjects in the Dikgale area of Limpopo Province in Northeastern South Africa, which found a similar prevalence level for elevated total cholesterol of 25.6%[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…which was a survey restricted to adults 35 years and older[ 8 ]. Manning et al (2016) identified a much higher prevalence rate of 69% for total cholesterol elevation (though a lower threshold of 4.5mmol/L) in Cape Town, but this was for obese subjects with ages 18 and older[ 9 ]. Finally, Maimela et al(2016) performed a survey of 20–59 year old subjects in the Dikgale area of Limpopo Province in Northeastern South Africa, which found a similar prevalence level for elevated total cholesterol of 25.6%[ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher total cholesterol is less common in the Black African population, though dyslipidemia overall is grossly similar to global averages[ 6 ]. Community level assessments have found prevalence rates of dyslipidemia between 14% and 69%[ 7 9 ].In South Africa, the treatment effects of HIV/AIDS complicate the picture of dyslipidemia[ 10 ]. This is particularly true given the well-known effect of protease inhibitors, a common component of antiretroviral therapy, which can elevate serum lipids by over 25% and accelerate progression towards cardiovascular events, but is also notable for first-line non-nucleoside and nucleoside reverse transcriptase inhibitors[ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…About 5 percent of the patients with non-communicable diseases were estimated to have been associated with obesity (Banjare and Bhalerao 2016). Obesity was also shown to exacerbate other intermediate risk factors and noncommunicable diseases and increase the risk of disability and mortality (Manning et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Kraja et al (2016) revealed that tobacco use, alcohol consumption, physical inactivity, unhealthy diet, and obesity are the behavioural risk factors for non-communicable diseases and many others account for 80% of mortality. Studies on the prevalence of such risk factors had been carried out in urban and rural villages around South Africa Maimela et al, 2016;Manning et al, 2016). Bearing in mind that the causes of NCDs may differ we conducted a study on the prevalence of behavioural risk factors in Collins Chabane municipality of Vhembe District.…”
Section: Introductionmentioning
confidence: 99%